2005
DOI: 10.1111/j.1600-051x.2004.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study to investigate an association between adverse pregnancy outcome and periodontal disease

Abstract: There was no association between the severity of periodontal disease and pregnancy outcome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
3
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 15 publications
6
65
3
11
Order By: Relevance
“…These parameters when they were used individually and when inferred together were indicative of periodontal infection and correlated with the adverse pregnancy outcome. The results in the present study are in accordance with the study conducted by Moore et al (2005) 15 who found the mean probing depth of 3.85 mm, Offenbacher (1996) 1 reporting the mean probing depth of 3.17 mm. In the study conducted by Lopez et al (2002) 9 examined all the teeth that were present in the dental arch with the mean probing pocket depth of 2.17 -2.94 mm.…”
Section: Discussionsupporting
confidence: 83%
“…These parameters when they were used individually and when inferred together were indicative of periodontal infection and correlated with the adverse pregnancy outcome. The results in the present study are in accordance with the study conducted by Moore et al (2005) 15 who found the mean probing depth of 3.85 mm, Offenbacher (1996) 1 reporting the mean probing depth of 3.17 mm. In the study conducted by Lopez et al (2002) 9 examined all the teeth that were present in the dental arch with the mean probing pocket depth of 2.17 -2.94 mm.…”
Section: Discussionsupporting
confidence: 83%
“…Based on these results they do not support a specific drive to improve periodontal health of pregnant women as a means of improving pregnancy outcomes [28]. Another study that did not find any significant relationship used partial mouth recordings which may underestimates the prevalence of periodontal disease [29]. An interventional study did not find a difference in the clinical periodontal status between preterm low birth weight cases and normal birth weight outcome.…”
Section: Discussionmentioning
confidence: 77%
“…Preeclampsia also involves increase in inflammatory cytokines in the blood stream, which makes adjusting for preeclampsia in our study important before any conclusion can be made. On the other hand, many studies did not find a positive correlation between periodontal disease and preterm labor [28][29][30][31][32]. Based on these results they do not support a specific drive to improve periodontal health of pregnant women as a means of improving pregnancy outcomes [28].…”
Section: Discussionmentioning
confidence: 80%
“…-le poids du nouveau-né [25][26][27][28][29][30][31][32][33][34] ; -la prématurité telle qu'elle a été définie précédemment (accouchement avant 37 SA quel que soit le poids du nouveau-né) [29][30][31][32][33][34][35][36][37][38][39][40] ;…”
Section: Définition De La Prématuritéunclassified